Utilization of information sources by farmers under different production systems in Uttaranchal and Uttar Pradesh - S.P. Gupta; Amardeep; Kushal Vir (Journal of Agricultural Extension Management, 2025)
The significance of information and communication in today’s society 1s apparent. Communication of new information, ideas and technology is an integral part of rural transformation. Many research studies; conferences and seminars have probed this area with a view to discuss some theoretical and practical issues for better utilization of communication and information sources by all the segments of the society for the benefit of society at large. Proper flow of information not only minimizes the communication gap but also opens avenues for people to get well informed. In India, nearly 70 per cent population resides in rural areas and derives their livelihood from agriculture and allied activities to round the year employment. Agricultural development in India largely depends on the action of its framing population scattered all over the country. Progress can only take place when the people know the new technology, understand it and act up upon it (Raj put R. 1993). This requires access to accurate and reliable information through appropriate and dependable sources. Thus the developmental activities cannot be pursued effectively in the absence of good communication infrastructure. Perhaps the oldest and most common approach of rural development communication in the less developed countries is the extension service for the dissemination of useful and practical information on agriculture, nutrition, health and family planning (Khan 1979).